An integrated model of pitch perception incorporating place and temporal pitch codes with application to cochlear implant research - Saeedi, Nafise Erfanian; Blamey, Peter; Burkitt, Anthony; Grayden, David (Elsevier Ltd., 2016)
Although the neural mechanisms underlying pitch perception are not yet fully understood, there is general agreement that place and temporal representations of pitch are both used by the auditory system. This paper describes a neural network model of pitch perception that integrates both codes of pitch and explores the contributions of, and the interactions between, the two representations in simulated pitch ranking trials in normal and cochlear implant hearing. The model can replicate various psychophysical observations including the perception of the missing fundamental pitch and sensitivity to pitch interval sizes. As a case study, the model was used to investigate the efficiency of pitch perception cues in a novel sound processing scheme, Stimulation based on Auditory Modelling (SAM), that aims to improve pitch perception in cochlear implant hearing. Results showed that enhancement of the pitch perception cues would lead to better pitch ranking scores in the integrated model only if the place and temporal pitch cues were consistent.
Keywords: Computational models; Auditory perception; Pitch ranking; Cochlear implant; Plasticity